Modeling the Detection of Early-Evolving Melanoma Symptoms: Role of Cancer Information and Delay Discounting. - Critchfield, Thomas; Howard, Niki (Psychological Record, 2016)
Young adults became familiar with sample images showing the presence and absence of melanoma symptoms, and on each of a series of subsequent test days rated whether a single lesion image had changed from the asymptomatic sample. In general, as symptom severity of the test lesions increased, participants became increasingly likely to report change, with no global differences apparent for groups distinguished by whether they encountered symptom evolution sooner versus later or whether they had or had not encountered cancer information similar to that used in melanoma patient education. Within groups there was considerable variability in individual detection behavior, and this variability correlated with a measure of delay discounting such that less impulsive individuals tended to detect smaller stimulus changes. Signal detection analysis revealed a general bias against reporting stimulus change, with more impulsive individuals showing more pronounced bias. In placing melanoma symptom detection behavior within an impulsivity framework, the present study suggests that a single approach to patient education may not be equally appropriate for all individuals.